Analisis Kebijakan Pesantren Ramah Anak dalam Perspektif Perlindungan Hak Anak di Lembaga Pendidikan Keagamaan - Abdul Aziz; Tiara Melani; Riyan Irhamsyah; Amelia Amelia; Maya Yunus (Jurnal Pendidikan dan Kebudayaan (JURDIKBUD), 2026)
The Child-Friendly Islamic Boarding School (Pesantren Ramah Anak/PRA) policy is a strategic effort to create a safe, inclusive, and child rights-oriented environment in Islamic boarding schools. This article analyzes the Child-Friendly Islamic Boarding School policy from the perspective of Islamic Education Management and its relationship with child rights protection in religious educational institutions. The research uses a qualitative approach through literature study and policy analysis of regulations, Islamic education management literature, and previous studies. Data analysis was conducted using content analysis techniques based on the functions of Islamic education management, namely planning, organizing, implementing, and supervising. The results of the study show that the Child-Friendly Islamic Boarding School policy is in line with the principles of Islamic Education Management, particularly the values of justice, trust, and benefit, but still faces implementation obstacles such as limited human resources, weak supervision, and resistance from the boarding school culture. This study confirms that the success of the Child-Friendly Islamic Boarding School policy depends on strengthening integrated and sustainable Islamic education management to ensure the protection of children's rights.